2023
DOI: 10.1513/annalsats.202205-461oc
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Use of Invasive and Noninvasive Mechanical Ventilation in Pediatric Asthma: 2009–2019

Abstract: Rationale: Despite lower overall hospitalization rates for asthma in recent years, there has been an increase in the number of pediatric patients receiving intensive care management in the United States.Objectives: To investigate how the use of invasive and noninvasive mechanical ventilation for asthma has changed in the context of an evolving cohort of critically ill pediatric patients with asthma.Methods: We analyzed children admitted to intensive care units for asthma from 2009 through 2019 in the Virtual P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Finally, our protocol did not include a standardized criteria to start HFNC. Given the national trend of trading conventional oxygen therapy via facemask with HFNC in pediatric critical asthma, 43 future interventions can aim to standardize the HFNC initiation in emergency rooms and PICUs.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, our protocol did not include a standardized criteria to start HFNC. Given the national trend of trading conventional oxygen therapy via facemask with HFNC in pediatric critical asthma, 43 future interventions can aim to standardize the HFNC initiation in emergency rooms and PICUs.…”
Section: Discussionmentioning
confidence: 99%
“…16 Despite the lack of high-quality evidence, HFNC is now ubiquitous to PICUs and its frequency of use in children with critical asthma is increasing. 5,17 In this issue of Pediatric Pulmonology, Maue et al 18 used standard quality improvement (QI) methodology combined with multivariable linear regression to evaluate the effect of adding a respiratory therapist (RT)-driven HFNC weaning protocol to their existing continuous albuterol weaning pathway for children with critical asthma. 19 The primary outcome was duration of HFNC therapy.…”
mentioning
confidence: 99%
“…However, one study 14 reported an association between HFNC use and a delay in initiating noninvasive ventilation (NIV) and a recent propensity‐scored matched study using an administrative database noted HFNC use was associated with longer hospital length of stay 16 . Despite the lack of high‐quality evidence, HFNC is now ubiquitous to PICUs and its frequency of use in children with critical asthma is increasing 5,17 …”
mentioning
confidence: 99%